Canine hepatozoonosis in Brazil: description of eight naturally occurring cases - Gondim, LFP; Kohayagawa, A.; Alencar, N. X.; Biondo, A. W.; Takahira, Regina Kiomi [UNESP]; Franco, SRV (Elsevier B.V., 1998)
Eight cases of canine hepatozoonosis were diagnosed at the Veterinary Hospital (Faculdade de Medicina Veterinaria e Zootecnia, Universidade Estadual Paulista, Campus de Botucatu), between October 1993 and April 1994. Clinical signs included anorexia, pale mucous membranes, weight loss, pain, diarrhoea, vomit, gait abnormalities, fever, polyuria and polydipsia. Haematologic findings revealed anaemia in seven cases, leucocytosis with neutrophilia in three cases, lymphopenia in three cases and monocytosis in four cases. Serum biochemistries included alterations in many parameters. Thr micrometry of Hepatozoon canis gametocytes ranged from 6.8 x 4.0 mu m to 7.5 x 4.5 mu m. Parasitaemia ranged from less than 0.5% to 2%. In all the cases reported other concurrent diseases were present. Diagnosis of canine hepatozoonosis was made by identifying H. canis gametocytes within leucocytes in stained blood smears. (C) 1998 Elsevier B.V. B.V.
Keywords: Hepatozoon canis; dog